REPRODUCING QUALITIES OF DIFFERENT AGE FINE - WOOL EWES IN THE CONDITIONS OF THE «R-KURTY» BREEDING FARM IN ALMATY REGION - Kulataev, B. T.; Kozhakhmetova, A. N. (Ғылым және білім №1, 2020)
The use of mobile artificial insemination, ovocytotoxic serum and sperm diluents, laser bioactivation provides the opportunity to obtain financial savings and increase the profitability of sheep breeding by 26-42% compared with the traditional way of conducting the industry The development of sheep husbandry, increasing the quantity and quality of products should be based on intensive and rational technologies that ensure the development of farms and the use of genetic resources of both local and local breeding animals on the basis of creating optimal conditions for growing. Scientific research was carried out on sheep of the Kazakh fine-wool breed bred in the Almaty region, primarily in the farm named after R-Kurty. To study the productive and biological characteristics of sheep, the Kazakh fine-wool breed was made in accordance with the standards of special scientific and production experiments. The study of biotechnological methods for the effectiveness of frozen sheep imported breeds The Rambouillet, The Polypei, The Suffolk, The Avacci and The Ost-freeze breeds and their use for ewes of the Kazakh fine-fleece breed and the biotechnological role in obtaining highly productive sheep breeds depending on gender. Использование передвижных пунктов искусственного осеменения маток, применение ОЦС и молочных разбавителей спермы, лазерная биоактивация обеспечивает возможность получения экономии финансовых средств и повышению рентабельности овцеводства на 26-42% по сравнению с традиционным способом ведения отрасли Развитие овцеводства, увеличение объемов и качества продукции должно опираться на интенсивные и рациональные технологии ведения отрасли в условиях фермерских хозяйств и использование генетического потенциала как отечественных, так и зарубежных пород овец, на основе создания оптимальных условий выращивания. Научные исследования проводились на овцах казахской тонкорунной породы разводимых в Алматинской области, прежде всего в племхозе имени Р-Курты. Для изучения продуктивных и биологических особенностей овец казахской тонкорунной породы при выполнении предусмотренных методикой целей были выполнены согласно схеме специальных научно-производственных опытов. Изучение биотехнологических метод эффективности замороженных семян баранов импортных пород рaмбульe, полипэй, cуффольк, aвaccи и оcт-фриз и их использование на овцематок казахской тонкорунной породы и биотехнологический роль в получение высокопродуктивных пород овец в зависимости от пола. Промышленное скрещивание маток с помесными баранчикам и баранами, способствовало получению помесных ягнят мясного типа.
Keywords: журнал кксон; рк; научный журнал; периодическое издание; отечественное издание; овцеводство; искусственное осеменение маток; скрещивание маток баранчиков; помесные ягнята мясного типа